Asymptomatic (Subclinical) Meningitis in One of Premature Triplets with Simultaneous Enteroviral Meningitis: A Case Report - Ashish Gupta; Robert W. Tolan Jr (Thieme Medical Publishers, Inc., 2012)
Most enterovirus infection in the neonate and young infant is asymptomatic, but serious disease may occur, especially if acquired perinatally. We report the first case, to our knowledge, of asymptomatic enterovirus aseptic meningitis, and of concurrent enterovirus aseptic meningitis in premature triplets. Ten-week-old, 31-week-estimated gestational age premature triplet boys were diagnosed with enterovirus aseptic meningitis on the same day. Two of the triplets developed symptoms on the day of admission, while the third remained symptom free throughout the infection. All three recovered completely and are healthy more than a decade later.